2014
DOI: 10.1037/a0033544
|View full text |Cite
|
Sign up to set email alerts
|

When are abrupt onsets found efficiently in complex visual search? Evidence from multielement asynchronous dynamic search.

Abstract: Previous work has found that search principles derived from simple visual search tasks do not necessarily apply to more complex search tasks. Using a Multi-element Asynchronous Dynamic (MAD) visual search task, where high numbers of stimuli could either be moving, stationary and/or changing in luminance, Kunar and Watson (2011) found that, unlike previous work, participants missed a high number of targets with search for moving items worse than for static and no benefit for finding targets that showed a lumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 87 publications
4
23
2
Order By: Relevance
“…Previous research has shown that there is a limit to what we can attend to (e.g., see Marois & Ivanoff, 2005 for a review), and that, when attention is occupied, then the processing of other information in our environment is impaired (e.g. Broadbent, 1958, Pashler, 1994, Rensink, 2002, Simons & Chabris, 1999, Kunar et al 2008, Kunar & Watson, 2011, 2014, Kunar, Thomas & Watson, 2017). Therefore, if resources were consumed processing the outlier number then there may not be sufficient remaining to process the target item, leading to a detriment in target detection.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that there is a limit to what we can attend to (e.g., see Marois & Ivanoff, 2005 for a review), and that, when attention is occupied, then the processing of other information in our environment is impaired (e.g. Broadbent, 1958, Pashler, 1994, Rensink, 2002, Simons & Chabris, 1999, Kunar et al 2008, Kunar & Watson, 2011, 2014, Kunar, Thomas & Watson, 2017). Therefore, if resources were consumed processing the outlier number then there may not be sufficient remaining to process the target item, leading to a detriment in target detection.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of which theory accounts for the dual-task interference effect, both the domain-general and domain-specific theories state that the magnitude of the interference effect should be influenced by conversation and/or task difficulty. For example, previous research has robustly shown that increasing task difficulty can lead to impairments in RTs and error rates (e.g., Kunar, Thomas, & Watson, 2017 ; Kunar & Watson, 2011 , 2014 ; Wolfe, Oliva, Horowitz, Butcher, & Bompas, 2002 ). That is, the more difficult a task is the more resources it will use, leaving fewer available for a second task, leading to greater dual-task impairments (e.g., Hitch & Baddeley, 1976 ; Kahneman, 1973 ; Sullivan, 1976 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a phenomenon named motion-induced blindness (Bonneh, Cooperman, & Sagi, 2001) has reportedly been used to demonstrate to aircraft pilots the importance of moving their head and eyes around when scanning the environment, preventing the pilot from focusing on one particular spot which can cause a failure to notice stationary objects. Other work has shown that people miss a large proportion of targets if they are rare or the display is complex, which has implications for real-world search tasks such as airport security/baggage screening or searching for anomalies in medical images (e.g., Kunar, Rich, & Wolfe, 2010; Kunar & Watson, 2011, 2014; Kunar, Watson, Taylor-Phillips, & Wolska, 2017; Russell & Kunar, 2012; Van Wert, Horowitz, & Wolfe, 2009; Wolfe, Horowitz, & Kenner, 2005; Wolfe et al, 2007). Accordingly, with the view that laboratory studies are useful tools to help in real-world tasks, in the present work we developed a demonstration of change blindness to be used in driver education.…”
Section: Introductionmentioning
confidence: 99%